CULTURAL BARRIERS - Egamberdiyeva Irodaxon; Abdurasulova Diyoraxon; Jo’rayeva Xurshida (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annatation: The article discusses the different types of cultural barriers that can hinder effective communication and interaction between people from different cultural backgrounds. It explores the various sources of cultural differences and how they can lead to misunderstandings and conflicts. The article also provides strategies for overcoming cultural barriers, such as cultural sensitivity and awareness, intercultural communication training, and collaboration.